PENGGUNAAN DAN MAKNA KATA "GAWE" TERHADAP KEBIASAAN MASYARAKAT PALEMBANG - Nyayu Lulu Nadya (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The Palembang community is a multiethnic society that is full of linguistic phenomena. Most of them are immigrants from outside Palembang, it will determine the use of the language used (Oktovianny, 2017: 895). Nowadays, in millenial generation, the use of Palembang language has become a language that mixes with other languages and can be mutually understood by fellow speakers. One of the words that is often used by the people of Palembang is gawe. In the Baso Palembang collection, the word gawe is defined as creating, working. The problem in this study was how the use and meaning of the word gawe to the habits of the Palembang people?. The purpose of this study was describe the use and meaning of the word gawe to the habits of the Palembang people. The type of research used in this study was qualitative research. In Sarosa (2017: 8), qualitative research is a study that attempts to understand the phenomenon in its setting and its natural context (not in the laboratory), i.e. the researcher does not attempt to manipulate the observed phenomena. In fact one word gawe can have many meanings when it is spoken by the Palembang people in everyday life for example, ado gawe, katek gawe, gawe apo, and apo gawe.Keywords— meaning, gawe, community, Palembang